Development of the genetic potential of the herd. "Key Indicators" - B.U.Yakubov; Zh.N.Khudzhamov; Kh.A.Mamatov (Genius Journals, 2022)
Creation of a strong thoroughbred herd.
Keywords: Farm; genetic potential; milk; cow